SQUIRE 2.0 (Standards for QUality Improvement Reporting Excellence): Revised Publication Guidelines From a Detailed Consensus Process. Issue 1 (January 2016) - Ogrinc, Greg; Davies, Louise; Goodman, Daisy; Batalden, Paul; Davidoff, Frank; Stevens, David
Abstract : Supplemental Digital Content is Available in the Text.